Controllability of threshold voltage in Ag-doped ZnO nanowire field effect transistors by adjusting the diameter of active channel nanowire - Kim, Kyoungwon; Debnath, Pulak Chandra; Park, Dong-Hoon; Kim, Sangsig; Lee, Sang Yeol (AMER INST PHYSICS, 2010)
Silver doped zinc oxide nanowires (NWs) were synthesized on (0001) sapphire substrate by hot-walled pulsed laser deposition. Both enhancement mode and depletion mode NW field effect transistors (FETs) were fabricated. The shift of threshold voltage of silver doped zinc oxide NW FET was observed from 2.45 to -3.2 V depending on the diameter of NWs without any significant changes of the subthreshold swing, carrier concentration, and on/off ratios. We demonstrate that the transfer characteristics of silver doped zinc oxide NW FETs were closely related with the size of NW diameter and control the shift of threshold voltage.
Keywords: THIN-FILM TRANSISTORS; ZINC-OXIDE; FABRICATION; ARRAYS